2022
DOI: 10.3390/ijms232213725
|View full text |Cite
|
Sign up to set email alerts
|

SNPs in 3′UTR miRNA Target Sequences Associated with Individual Drug Susceptibility

Abstract: The complementary interaction of microRNAs (miRNAs) with their binding sites in the 3′untranslated regions (3′UTRs) of target gene mRNAs represses translation, playing a leading role in gene expression control. MiRNA recognition elements (MREs) in the 3′UTRs of genes often contain single nucleotide polymorphisms (SNPs), which can change the binding affinity for target miRNAs leading to dysregulated gene expression. Accumulated data suggest that these SNPs can be associated with various human pathologies (cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…miRNAs can regulate the expression of target genes by influencing the stability of target gene mRNAs or blocking the translation process to exert their functions [ 48 , 49 , 50 ]. This study demonstrated that miR-128-3p in KGN cells can target GHSR to inhibit the expression of GHSR proteins.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can regulate the expression of target genes by influencing the stability of target gene mRNAs or blocking the translation process to exert their functions [ 48 , 49 , 50 ]. This study demonstrated that miR-128-3p in KGN cells can target GHSR to inhibit the expression of GHSR proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on ethnic differences, the findings may only apply to the Taiwanese population. Additionally, because the materials of the reporter assay used in the promoter–reporter cannot be shared with the 3’UTR-reporter, and the 3’UTR-reporter assay needs to consider the influence of microRNA [ 46 ], only the promoter region was discussed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…miR-218 epigenetic silencing influenced by Rictor upregulation initiates the mTOR-Akt signaling cascade, thereby contributing to oral carcinogenesis [ 16 ]. The 3′UTRs miRNA recognition elements (MREs) of genes often have single nucleotide polymorphisms (SNPs) that modify the target microRNA binding affinity resulting in gene expression dysregulation [ 17 ]. Ovarian cancer patients with the 3′ UTR rs4245739 SNP have a reduced chance of survival because it creates an unsuitable target site for miR-191.…”
Section: Introductionmentioning
confidence: 99%